PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP TINGKAT PENJUALAN PADA PAPA RON’S PIZZA TEUKU UMAR – DENPASAR - Ni Luh Putu Ari Sukawirantini (Majalah Ilmiah Widyacakra, 2019)
The Title Research is The Influence of Product Quality and Service Quality on Level of Sales at Papa Ron’s Pizza Teuku Umar Denpasar.The types of product quality and service quality are diverse, business people are required to create the right strategy. If consumers are satisfied with the services provided, the company can get a profit which can increase sales volume. This research aimed to analyze the influence of product quality and service quality on level of sales at Papa Ron’s Pizza Teuku Umar Denpasar. The sample of this research is 85 respondents of guests at Papa Ron’s Pizza Teuku Umar Denpasar. The Data sources used in this research are primary and secondary data. Data is analyzed using path analysis that is assisted with SPSS for Windows version 22. Data collection method in this research using interview method, bymeans of questionnaires with likert scale. The analytical technique used is multiple linier regression analysis. Results of statistical analysis known that the product quality and service quality influenced on level of sales at Papa Ron’s Pizza Teuku Umar Denpasar is 41,4%, based on hypothesis testing with the F and t test results, it can be concluded that the product quality variable (X1) and service quality (X2) simultaneously (together} and significantly influence on level of salesvariable (Y) with value of F-test is 28,976 and sig 0,000. The product quality variable (X1) partially and significantly positive influenced on level of sales (Y) with value of t-test is 5,101 and sig. 0,000 and service qualityvariable (X2) significantly positiveinfluenced on level of sales variable (Y) with value of t-test is 4,564 and sig. 0,000 at Papa Ron’s Pizza Teuku Umar Denpasar.